2010
DOI: 10.1177/156482651003100223
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant and Young Child Feeding Practices in Sri Lanka: Secondary Data Analysis of Demographic and Health Survey 2000

Abstract: Background. Poor feeding practices in early childhood contribute to the burden of childhood malnutrition and morbidity.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 7 publications
10
42
2
1
Order By: Relevance
“…Another factor having an adverse association with EBF was urban residence as these women were more likely to bottle-feed their babies, a finding which is similar to Sri Lanka (23) . In Bangladesh urban mothers did not initiate timely breast-feeding for their infants (32) .…”
Section: Discussionmentioning
confidence: 67%
“…Another factor having an adverse association with EBF was urban residence as these women were more likely to bottle-feed their babies, a finding which is similar to Sri Lanka (23) . In Bangladesh urban mothers did not initiate timely breast-feeding for their infants (32) .…”
Section: Discussionmentioning
confidence: 67%
“…Our results indicated that infant and young child feeding practices in the South Asia region have not reached the expected levels that are required to achieve a substantial reduction in child a. The adjusted odds ratios for these factors from the multiple logistic regression models can be found in table 5 in the papers in this Special Section from Bangladesh [17], India [18], and Nepal [19] and in table 4 in the paper from Sri Lanka [20]. b.…”
Section: Discussionmentioning
confidence: 74%
“…a. The adjusted odds ratios for these factors from the multiple logistic regression models can be found in table 5 in the papers in this Special Section from Bangladesh [17], India [18], Nepal [19], and Sri Lanka [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of the study was comparable to the 2011 Ethiopian DHS report (52%), the 2005 Ethiopian DHS report (49%), a study done in Harar Ethiopia (51.9%), Tanzanian 2010 national DHS report (49.9%), and a study done in the district of peninsular Malaysia (43.1%) [6,[10][11][12][13]. But the finding was lower than studies done in the Sri Lanka national DHS report (60.6%), Dinajpur district of Bangladesh (61.3%), in Legon district of Ghana (66%), in Dodoma municipality of Tanzania, in the rural district of Hoima of western Uganda (57%), and in Goba district of Ethiopia (73.5%) [14][15][16][17][18][19] …”
Section: Prevalence Of Ebfmentioning
confidence: 98%